2017
DOI: 10.1016/j.neuroscience.2016.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anxiety on prefrontal cortex encoding of cognitive flexibility

Abstract: Anxiety often is studied as a stand-alone construct in laboratory models. But in the context of coping with real-life anxiety, its negative impacts extend beyond aversive feelings and involve disruptions in ongoing goal-directed behaviors and cognitive functioning. Critical examples of cognitive constructs affected by anxiety are cognitive flexibility and decision making. In particular, anxiety impedes the ability to shift flexibly between strategies in response to changes in task demands, as well as the abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
112
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(127 citation statements)
references
References 135 publications
(169 reference statements)
11
112
1
3
Order By: Relevance
“…It has been shown that the changes in anxiety- and depressive-like behavior were correlated with increased levels of dopamine and dopamine metabolites in the midbrain [55]. Our study found that CBF was highly correlated (inversely) with anxiety level, which is consistent with previous findings [46]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It has been shown that the changes in anxiety- and depressive-like behavior were correlated with increased levels of dopamine and dopamine metabolites in the midbrain [55]. Our study found that CBF was highly correlated (inversely) with anxiety level, which is consistent with previous findings [46]. …”
Section: Discussionsupporting
confidence: 92%
“…Studies have shown that neurovascular risk is highly associated with accelerated decline in language ability, verbal memory, attention and visuospatial abilities [2, 3]. Reduced CBF is linked to anxiety and depression [46], and impaired BBB is associated with neuroinflammation and synaptic dysfunction [7]. These neurovascular deficits are exacerbated with age [8] and in a more rapid and profound fashion in neurodegenerative disorders, including Alzheimer's disease (AD) [912].…”
Section: Introductionmentioning
confidence: 99%
“…The neurovascular risk is highly associated with accelerated decline in executive functions and cognition, including language, verbal memory, attention and visuospatial abilities [2, 3]. Mental health, such as anxiety and depression, is also link to reduced CBF [46], similar to our observations in animal models [50]. …”
Section: Neuroimaging Biomarkers For Human Aging and Cr Interventionssupporting
confidence: 73%
“…Similarly, studies have shown that neurovascular risk is highly associated with accelerated decline in language ability, verbal memory, attention and visuospatial abilities [2, 3]. Reduced cerebral blood flow (CBF) is linked to anxiety and depression [46], and impaired blood-brain barrier is associated with neuroinflammation and synaptic dysfunction [7]. These metabolic and hemodynamic reductions precede brain structural alteration (gray matter and white matter atrophy) and cognitive impairment [810].…”
Section: Introductionmentioning
confidence: 99%
“…Infralimbic cortex has strong functional connections with amygdala (Kim, Gee, Loucks, Davis, & Whalen, 2011), and these projections are essential for effective extinction of fear responses (Bloodgood, Sugam, Holmes, & Kash, 2018;Sierra-Mercado, Padilla-Coreano, & Quirk, 2011). Currently, the functional effects of infralimbic projections to BNST have not been examined, so further study of the impact of anxiety or threat on neural activity within the frontal cortex is needed (Park & Moghaddam, 2017). This is especially true for understanding frontal cortex function in humans.…”
Section: Anxiet Y-related Behaviormentioning
confidence: 99%